Fostering Learning, Building Futures: Education-Based Community Service Initiatives in Hasatan Julu - Rd. Heri Solehudin (Rahis Cendekia Indonesia, 2024)
This study explores the implementation and impact of education-based community service initiatives conducted in Hasatan Julu, a rural village facing various educational challenges. Using a qualitative descriptive method, data were gathered through observations, interviews, and documentation involving university volunteers, teachers, parents, and local leaders. The findings revealed several positive outcomes, including increased student engagement, enhanced teaching practices, and improved parental involvement. The program also served as a platform for mutual learning, fostering personal and professional growth among the volunteers. However, concerns about sustainability were noted, highlighting the need for ongoing support and community capacity building. This research emphasizes the importance of participatory, inclusive, and context-sensitive approaches in improving educational quality in remote areas.